Escuela de futbol sala para la práctica deportiva en los grupos de adolescentes del recinto San José de la Parroquia Antonio Sotomayor del cantón Vinces, Provincia Los Ríos - Avilez Garcia, Estiven Humberto (2022)
The purpose of this research was to implement a futsal school for sports practice in groups of adolescents from the San José campus of the Antonio Sotomayor parish of the Vinces Los Ríos canton. The quantitative method and field research were used, describing and analyzing the variables of the study phenomenon through the incidence and its relationships in time and space, and 20 adolescents were intentionally selected, from which it was possible to obtain the necessary and pertinent information to the investigation, verifying that in the context of the study phenomenon the little sport practice in the groups of adolescents is reflected, arriving at the general conclusion allowed to establish the feasibility for the operation of a futsal school the same which is a sport that is practiced collectively for the practice of sports that consists of carrying out specific physical activity with a competitive desire and in which a series of rules must be respected in the group of adolescents of the San José campus of the Antonio Sotomayor parish of the Vinces canton.